ANALYSIS FUNCTION AND EFFICIENCY MARKETING OF ONION (Allium Ascalonicum) AT SUNGAI GERINGGING VILLAGE KAMPAR KIRI DISTRICK IN KAMPAR REGENCY - Ermi Tety; Eliza '; Rista Hardi Priyana (PEKBIS, 2015)
The objectives of this research were to 1). Know the function, channel and marketing agencies onion. 2). Analyze costs, margins, profibality, efficiency and the share of the farmer. This study usues survey, sampling was done by purposive sampling of 30 samples onion farmers at Sungai Geringging Kampar Kiri districk in Kampar regency. Taking sample of trader used snowball sampling by following marketing channel. The outcome of this research indicated the function-function of onion marketing at Sungai Geringging such as buy function, sale function, clean function, storage function, transportation function, standardization function, risk tackling function, market information function and financial capital function. The most efficient channel is channel 1, starting from farmer – trader of collector – trade of retailer – consumen. Total cost of marketing collector is Rp 416,67/kg and trade of retailers is Rp 153,02/kg. Marketing margins is Rp 3.166,67/kg, total profit is Rp 2.596,98/kg, the efficiency is 2,46% and the share of the farmer is 86,33%.Keywords: Marketing, function, channel, margins, efficiency.